Flower morpho-anatomy in Epiphyllum phyllanthus (Cactaceae) - De Almeida, Odair José Garcia [UNESP]; Sartori-Paoli, Adelita Aparecida [UNESP]; De Souza, Luiz Antonio (My University, 2010)
The aim of this contribution was to analyze the morpho-anatomical floral structure of Epiphyllum phyllanthus (L.) Haw., a widely distributed species across South America, occurring in humid forests as an epiphyte. Flowers and flower buds were collected in Maringá, Paraná State, Brazil, fixed, processed, and analyzed under light microscope and scanning electron microscope. The flower is sessile and epigynous with a well-developed hypanthium. All flower whorls have uniseriate epidermis. Secretory cavities containing mucilage and calcium oxalate crystals occur throughout the floral parenchymatous tissue. The androecium has many stamens with tetrasporangiate and bithecal anthers. The wall of the young anther is formed by epidermis, endothecium, a middle layer, and binucleate secretory tapetum that eventually becomes uninucleate. The gynoecium is syncarpous with 9-10 carpels, pluriovulate, and with parietal placentation. The ovary has inverted vascular bundles in a similar pattern as in Pereskia. The nectariferous region occurs on the inner surface of the hypanthium. The stigma has 9-10 lobes with a secretory epidermis. The ovules are circinotropous, bitegmic, crassinucelate, and have long funiculus as in many other Cactaceae.
Keywords: Anther; Gynoecium; Hypanthium; Nectary; Ovule